Iron isotope fractionation during mid-ocean ridge basalt (MORB) evolution: Evidence from lavas on the East Pacific Rise at 10°30′N and its implications. (15th December 2019) - Chen, Shuo; Niu, Yaoling; Guo, Pengyuan; Gong, Hongmei; Sun, Pu; Xue, Qiqi; Duan, Meng; Wang, Xiaohong
Abstract: Whether the Earth's mantle has a chondritic δ 56 Fe (deviation in 56 Fe/ 54 Fe from the IRMM-014 standard in parts per thousand) value or not remains under debate. The current view is that the observed average δ 56 Fe of mid-ocean ridge basalts (MORB) cannot be explained by partial melting of mantle source with chondritic value alone. Here, we report Fe isotope compositions on 29 MORB glasses sampled along a flowline traverse across the East Pacific Rise (EPR) axis at 10°30′N. These glasses show large MgO variation (1.8–7.4 wt.%) that forms a compositional continuum resulting from varying extent of fractional crystallization, which is accompanied by systematic Fe isotopic variation. Fractional crystallization modeling suggests that early crystallization of olivine, pyroxene and plagioclase gives rise to an iron enrichment trend and an increase in δ 56 Fe. Once Fe-Ti oxides appear on the liquidus and begin to crystallize, the FeO t and TiO2 contents of the residual melt decrease rapidly, which lead to a slight decrease in δ 56 Fe. These observations indicate that significant Fe isotope fractionation can indeed take place during MORB melt evolution. Hence, δ 56 Fe values of variably evolved MORB melts do not represent those of primary MORB melts and thus cannot be used to infer mantle source Fe isotope compositions. Importantly, δ 56 Fe values of primary MORB melts after correction for the effect of fractional crystallization can be well reproduced by mantle melting. Therefore, our study supports the idea that the Fe isotope composition of the accessible Earth is close to be chondritic. We note that conclusion would assume that the core, which takes up ∼90% of the Earth's Fe, must have a chondritic Fe isotope composition.